1924
DOI: 10.1021/ie50169a013
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Accelerators during Vulcanization - VI. Organic Acids and Inorganic Accelorators

Abstract: leather of pH = 9 gained 13.8 per cent in weight even though it lost some tannin, showing a very pronounced oxidation of the alcohol followed by aldehyde tannage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1927
1927
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The rubber and pigments were standardized in regard to chemical and physical properties and the various compounds prepared under the same milling conditions. Uncured compounds were studied microscopically Note-In general, this consisted of breaking down 400 grams of rubber for 4 minutes on 12-inch (30-cm.) laboratory mills, adding the pigments and sulfur as quickly as possible, and then sheeting off to 100 gage.…”
Section: Methodsmentioning
confidence: 99%
“…The rubber and pigments were standardized in regard to chemical and physical properties and the various compounds prepared under the same milling conditions. Uncured compounds were studied microscopically Note-In general, this consisted of breaking down 400 grams of rubber for 4 minutes on 12-inch (30-cm.) laboratory mills, adding the pigments and sulfur as quickly as possible, and then sheeting off to 100 gage.…”
Section: Methodsmentioning
confidence: 99%
“…Basic Industries-Basic industries whose raw material is, for the most part, not processed and whose products in the main are the raw materials for other industries must, to succeed, locate near cheap fuel or cheap power. It is true that major raw materials must be obtainable (1) advantageously as to quality and price, or at least (2) on a competitive basis with the same industries in other localities; but these two factors alone will not serve to establish a basic industry, for basic industries demand cheap fuel and advantageous raw materials in order to compete in the national market. It is…”
Section: Inmentioning
confidence: 99%
“…According to the systems usually in vogue the water is treated very much after the fashion of the Oberlin plant so far as the addition of the chemicals is concerned. But the usual method, and the one used in Oberlin for several years, is to leave the treated water in a settling basin for about 18 hours and then run it directly onto the sand filters. This method, however, caused considerable trouble.…”
Section: After-precipitationmentioning
confidence: 99%
“…This suggested that there might be present in the acetone extract a very minute amount of a 1' British Patent 260,001 (1926). 18 J. Chem. Soc.…”
mentioning
confidence: 99%